Students' Cognitive Process to Solve Mathematics Problems Based on Learning Style - Binur Panjaitan (AL-ISHLAH: Jurnal Pendidikan, 2023)
The purpose of this study was to describe the cognitive processes of students in solving mathematical problems. This research is a qualitative exploratory research. Researchers explore things that affect the occurrence of the subject's cognitive processes through in-depth interviews. Subjects were selected based on the results of the study of learning styles. The subject of this research is one student with visual, one auditory, one kinesthetic and one tactile learning styles. To investigate student learning styles, the interpretation of Perceptual Learning Style elements is used. The stages of problem solving in this research are to understand the problem, make a plan of completion, complete according to plan and look back. Mathematical problems from story problems and proof problems. Data from interviews and written work that have been valid were analyzed by examining how the subject's cognitive process towards the problem. The results showed that there were differences in the cognitive processes of visual, auditory, kinesthetic and tactile subjects in solving mathematical problems, both in story problems and in proof questions.